Impact of Childhood Adversity on Late-Life Cognition in Older Puerto Rican Adults - Lian, James; Crowe, Michael; Anstey, Kaarin J; Kiely, Kim M; Luisa Dávila, Ana; Andel, Ross (The journals of gerontology. Series B, Psychological sciences and social sciences, 2025)
OBJECTIVES: This study examined the association between childhood adversity and late-life cognitive outcomes among older Puerto Rican adults. METHODS: Data were from the Puerto Rican Elder: Health Conditions study, a population-based cohort of 3,713 older Puerto Rican adults (mean age 72.5 years; 60% female). Adverse childhood experiences were categorized into four factors: economic hardship, parental illiteracy, childhood illness, and neighborhood disadvantage. Cognition was assessed with the Mini-Mental Cabán (MMC). For our analyses, cognitive impairment was defined as scoring 1.5 standard deviations below the expected score, adjusted for age, sex, education, and reading ability. Ordinal logistic regression (baseline) and generalized linear mixed models (all 3 waves) analyzed MMC scores; generalized estimating equations assessed incident cognitive impairment (Waves 2 and 3). RESULTS: All four adversity factors were associated with poorer MMC scores at baseline. Parental illiteracy (β = -0.35, p < .001) and neighborhood disadvantage (β = -0.27, p < .001) showed stronger associations than economic hardship (β = -0.10, p = .003) and childhood illness (β = -0.21, p < .001). No factors were significantly related to changes in cognitive scores over time. Depressive symptoms and self-rated health partially mediated cross-sectional relationships, with depressive symptoms showing a stronger effect. All adversity factors except economic hardship were linked to baseline cognitive impairment (OR = 1.42 parent illiteracy, OR = 1.24 childhood illness, OR = 1.82 neighborhood disadvantage, p < .05). Only neighborhood disadvantage was associated with incident cognitive impairment (OR = 1.19, p = .003). DISCUSSION: This study highlights the lasting effect of childhood adversity on late-life cognitive health among older Puerto Ricans, suggesting that addressing early adversity may promote cognitive health later in life.
Keywords: senioři; Cognitive Dysfunction; Neighborhood Characteristics; senioři nad 80 let; Hispánci a Latinoameričané; Cognition; nepříznivé zkušenosti z dětství; mužské pohlaví; Adverse Childhood Experiences; Hispanic or Latino; Mental health in later life; Early adversity and aging; Adverse childhood experiences; Cognitive decline; kognice; chudoba; Aged, 80 and over; Older Hispanic adults; ženské pohlaví; Humans; kognitivní dysfunkce; charakteristiky okolí bydliště; Portoriko; Aged; Female; Poverty; Puerto Rico; lidé; Male